2012
DOI: 10.5704/moj.1203.004
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Osteochondroma in Elbow Joint: A case report

Abstract: soft tissue tumour, chondroma, osteochondroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…More specifically, they found that 49% were located at the fingers, 15% at the hands, 11% at the toes, 10% at the feet, 4% at the forearms, and 11% at other sites. ESCs have also been described in the popliteal region [13] , Hoffa's infrapatellar fat [14] , [15] , wrist [16] , elbow joint [17] , while some more rare locations can be the gluteal region [18] , diaphragm [19] , anterior abdominal wall [20] , axilla [21] , scalp [22] , preauricular region [4] , dura [23] , larynx [24] , pharynx [25] , neck [26] , oral cavity [27] , skin [28] , fallopian tube [29] , and parotid gland [30] .…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, they found that 49% were located at the fingers, 15% at the hands, 11% at the toes, 10% at the feet, 4% at the forearms, and 11% at other sites. ESCs have also been described in the popliteal region [13] , Hoffa's infrapatellar fat [14] , [15] , wrist [16] , elbow joint [17] , while some more rare locations can be the gluteal region [18] , diaphragm [19] , anterior abdominal wall [20] , axilla [21] , scalp [22] , preauricular region [4] , dura [23] , larynx [24] , pharynx [25] , neck [26] , oral cavity [27] , skin [28] , fallopian tube [29] , and parotid gland [30] .…”
Section: Discussionmentioning
confidence: 99%